Uma Abordagem anal?tica para an?lise n?o-linear dos amplificadores de RF voltada para as estruturas do tipo FET - Campos, Marcel Veloso (2005)
Abstract: One of the most important characteristics to be maintained with respect to the quality of generic RF amplifiers is the linearity since that the absence of it can generate a series of effects and distortions in the signal to be transmitted. With this constant demand of the discovery of new technologies many additional impositions are imposed on the transmission equipments, which require an accurate treatment of the non-linear property that appears whenever in modern TV transmission systems. Ideally, always we try to reach the linear condition of operation and in consequence, the output signal must to be a rejoinder of the input one. In this case, it is possible to detect only some variations on the amplitude in a constant way as well as on the phase in a linear way. The main purpose of this dissertation is to present the theoretical approach for the treatment of the non-linearity when the electronic structure of the amplifier is totally built on the FET devices. Although, did not appear in the current literature any modeling with respect to the classical theory in this field of research, the approach adopted in this work not only can be extended for MOS, MES and LDMOS structures without no additional essential changes but also can be applied for amplifiers that have non-linear characteristics with higher order. Index Terms: Non-Linearity, Quadratic Behavior, RF Power Amplifiers, Harmonic Distortions.